2018
DOI: 10.1038/s41398-018-0192-9
|View full text |Cite
|
Sign up to set email alerts
|

Review of withdrawal catatonia: what does this reveal about clozapine?

Abstract: Withdrawal symptoms are common upon discontinuation of psychiatric medications. Catatonia, a neuropsychiatric condition proposed to be associated with gamma-aminobutyric acid (GABA) hypoactivity due to its robust response to benzodiazepines, has been described as a withdrawal syndrome in case reports but is not a well-recognized phenomenon. The authors undertook a review of withdrawal catatonia with an aim to understand its presentation as well as the medications and psychoactive substances it is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 105 publications
2
96
1
1
Order By: Relevance
“…Withdrawal cases collected here were recorded according to the related PTs defined in the MedDRA dictionary [35], where withdrawal is described as "the abrupt cessation of a drug use in a habituated person; and a substance specific syndrome following cessation or reduction in intake of a psychoactive substance previously used regularly". Clozapine withdrawal/discontinuation ADRs were the most frequently reported and, as such, current findings confirmed and expanded on previous anecdotal data [6,53,54]. In association with a sudden discontinuation of clozapine, which may be required in cases of blood dyscrasia or suspected myocarditis, instances of withdrawal have already been reported [6,44,54,55].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Withdrawal cases collected here were recorded according to the related PTs defined in the MedDRA dictionary [35], where withdrawal is described as "the abrupt cessation of a drug use in a habituated person; and a substance specific syndrome following cessation or reduction in intake of a psychoactive substance previously used regularly". Clozapine withdrawal/discontinuation ADRs were the most frequently reported and, as such, current findings confirmed and expanded on previous anecdotal data [6,53,54]. In association with a sudden discontinuation of clozapine, which may be required in cases of blood dyscrasia or suspected myocarditis, instances of withdrawal have already been reported [6,44,54,55].…”
Section: Discussionsupporting
confidence: 88%
“…Clozapine withdrawal/discontinuation ADRs were the most frequently reported and, as such, current findings confirmed and expanded on previous anecdotal data [6,53,54]. In association with a sudden discontinuation of clozapine, which may be required in cases of blood dyscrasia or suspected myocarditis, instances of withdrawal have already been reported [6,44,54,55]. It is of clear interest that a case of clozapine withdrawal neonatal syndrome was specifically mentioned here as well.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, psychotherapy may or may not be helpful [16, 42]. Finally, the safe management of discontinuation of increasingly prevalent combinations of psychotropic drugs presents a challenge [10]. One study found that changing from one antipsychotic to another, at least, could be done as safely with immediate drug-switching as with widely employed “cross-tapering” of doses downward of a discontinued, and upward of a replacement antipsychotic [43].…”
Section: Withdrawal Reactionsmentioning
confidence: 99%
“…Abrupt discontinuation of psychotropic drugs is very common in pregnancy, with greatly increased risk of adverse clinical effects on the mother and unknown impact on the fetus [36, 37]. Additional potential complications include shifts in the metabolic elimination of other prescribed medicines with which SRIs can interact pharmacokinetically [10, 34]. …”
Section: Withdrawal Reactionsmentioning
confidence: 99%
See 1 more Smart Citation